Reducing change management complexity: aligning change recipient sensemaking to change agent sensegiving. (7th December 2012) - Kumar, Payal; Singhal, Manish
Implementation of change in an organisation through culture can elicit a wide array of reactions from organisational members, spanning from acceptance to resistance. Drawing on Hatch's cultural dynamics model and on Wegner's social theory of learning, this paper dwells on an underdeveloped area in the extant literature, namely understanding change from the perspective of the change recipient, and then analysing how this is linked to the broader framework of organisational change. It is suggested that in order to drive meaningful change strategy, change agents need to learn that sensegiving imparted by them needs to be closely aligned to the sensemaking of change recipients at three levels of analysis.